2022
DOI: 10.1159/000524752
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Impact on Temporal Treatment Trends in Oropharyngeal Carcinoma: 2010–2016

Abstract: <b><i>Introduction:</i></b> The study objective was to identify practice patterns in oropharyngeal cancer management from 2010 to 2016 among human papillomavirus (HPV)-associated and non-HPV-associated oropharyngeal squamous-cell carcinoma (OPSCC) patients. <b><i>Methods:</i></b> The National Cancer Database was utilized to identify OPSCC patients from 2010 to 2016. Frequency distributions and multivariable analyses were generated to identify practice pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
1
1
Order By: Relevance
“…In the present study, however, 20.3% of HBH were academic centers. Previous literature has shown that patients treated at academic centers are more likely to be treated surgically, treated with TORS, and have better overall survival 20–22 . In an additional exploratory analysis, however, we found that high safety‐net burden academic centers treat fewer patients with surgery, when compared to lower safety‐net burden academic centers.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…In the present study, however, 20.3% of HBH were academic centers. Previous literature has shown that patients treated at academic centers are more likely to be treated surgically, treated with TORS, and have better overall survival 20–22 . In an additional exploratory analysis, however, we found that high safety‐net burden academic centers treat fewer patients with surgery, when compared to lower safety‐net burden academic centers.…”
Section: Discussioncontrasting
confidence: 46%
“…Previous literature has shown that patients treated at academic centers are more likely to be treated surgically, treated with TORS, and have better overall survival. [20][21][22] In an additional exploratory analysis, however, we found that high safety-net burden academic centers treat fewer patients with surgery, when compared to lower safety-net burden academic centers. These findings highlight that the treatment disparities in safety-net burden facilities may apply to academic and community facilities alike.…”
Section: Discussionmentioning
confidence: 76%